1989
DOI: 10.2136/sssaj1989.03615995005300020047x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mineral Weathering Trends Between Two Management Systems on a Catena of Loess‐Derived Soils

Abstract: This study was an attempt to predict potential long‐term mineralogical transformation trends in soils under continuous no‐tillage management using the in situ soil solution composition as a sensitive index of changes occurring in the soil system. Mineralogical and soil solution compositions of surface and subsurface horizons of a catena of loess‐derived soils (Memphis, Grenada, Calloway) under continuous (16 yr) no‐till (NT) and conventional‐till (CT) management suggested a shift in weathering patterns as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…This possible combined effect of pH (liming) and organic matter will need to be assessed in future studies in long-term experiments to deepen the understanding of possible management minerals with extensive intercalation (HIS-E or HIV-E) into those with partial intercalation (HIS-P or HIV-P). According to Karathanasis et al (1989), this does not necessarily lead to a reversal of the weathering sequence in this soil, but shows that the soil system has been altered in such a way that the precursor or intermediate minerals (2:1 clay minerals with partial intercalation with Al hydroxyl) may be becoming stable in the new pedo-environment.…”
Section: Composition Of Solution Of a Subtropical Oxisol Under Convenmentioning
confidence: 92%
See 3 more Smart Citations
“…This possible combined effect of pH (liming) and organic matter will need to be assessed in future studies in long-term experiments to deepen the understanding of possible management minerals with extensive intercalation (HIS-E or HIV-E) into those with partial intercalation (HIS-P or HIV-P). According to Karathanasis et al (1989), this does not necessarily lead to a reversal of the weathering sequence in this soil, but shows that the soil system has been altered in such a way that the precursor or intermediate minerals (2:1 clay minerals with partial intercalation with Al hydroxyl) may be becoming stable in the new pedo-environment.…”
Section: Composition Of Solution Of a Subtropical Oxisol Under Convenmentioning
confidence: 92%
“…The organic matter accumulation in the top soil layer under NT contributed to a three-fold increase in the content of dissolved organic carbon (DOC) over the CT soil. DOC can be associated with the significant Al increase (not found in the sorption complex) and Si in the solution of NT soils (Karathanasis & Wells, 1989). According to Azevedo et al (1996), the effect of NT on the soil solution can also be shown in the increase of S in solution, mainly derived from the mineralization of organic matter.…”
Section: Chemical Composition Of Soil Solutionmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, the degree of humification differed markedly (Mendonza et al, 2000;Guimarães et al, 2013) and was higher in the mechanically harvested area. The increased humification of this area, together with the increased MCD values of goethite in it, suggests a tendency toward a new dynamic equilibrium via gradual mineralogical changes in the soil system (Karathanasis & Wells, 1989). Inda Jr. & Kämpf (2005) examined the selective dissolution of Fe oxides and concluded that goethite heterogeneity was possibly a result of pedoenvironmental changes during the pedogenetic process; such changes altered the factors governing Al 3+ activity in the soil solution (e.g.…”
Section: Resultsmentioning
confidence: 99%